1988
DOI: 10.1111/j.1570-7458.1988.tb01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in locomotion between laboratory strains of Trichogramma maidis and its impact on parasitism of eggs of Ostrinia nubilalis in the field

Abstract: The locomotion of females of different strains of the parasitic wasp Trichogramma maidis (Hymenoptera, Trichogrammatidae) was measured under standardized conditions and compared to their efficiency in the field for several years. A manual and an automatic method for recording and analysing the locomotion of insects are described and results for differently reared laboratory strains of T. maidis are presented. The correlation between manual and automatic measurements of the travel speed was significant (r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
7

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 7 publications
3
45
0
7
Order By: Relevance
“…They chose to evaluate dispersal as a parameter because of its importance for field and greenhouse efficacy. Earlier, Bigler et al (1988) worked on this issue, and found that a correlation existed between locomotion rate (= travel speed) and parasitization (= efficiency) in the field of different Trichogramma maidis Pintureau and Voegelé strains. Although they developed a scientifically attractive approach, the methodology was rather time consuming to apply and was considered too complicated for mass rearing companies.…”
Section: Quality Control Guidelines For Egg Parasitoidsmentioning
confidence: 97%
See 1 more Smart Citation
“…They chose to evaluate dispersal as a parameter because of its importance for field and greenhouse efficacy. Earlier, Bigler et al (1988) worked on this issue, and found that a correlation existed between locomotion rate (= travel speed) and parasitization (= efficiency) in the field of different Trichogramma maidis Pintureau and Voegelé strains. Although they developed a scientifically attractive approach, the methodology was rather time consuming to apply and was considered too complicated for mass rearing companies.…”
Section: Quality Control Guidelines For Egg Parasitoidsmentioning
confidence: 97%
“…Since attributes like locomotory activity (Bigler et al 1988), host acceptance (van Bergeijk et al 1989), host suitability (van Bergeijk et al 1989) and temperature tolerance were negatively 1975in Switzerland (after Bigler 1994 affected by the former rearing system, we developed a new production unit. At the same time, risk evaluations of other deteriorations in the strain were performed and methods for measuring single traits and the field performance were developed.…”
Section: Obstacles In Mass-rearing Of Arthropodsmentioning
confidence: 99%
“…Bigler et al (1988) found that differences in the speed of movement of a number of strains of Trichogramma maidis Pintoureau & Voege. in the laboratory corresponded with their performance in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Walking behaviour of several Trichogramma strains has been studied by Bigler et al (1988), showing that there is a correlation of insect walking activity with parasitism in the field. These results imply that walking can be a useful parameter for quality control testing of Trichogramma.…”
Section: Key-wordsmentioning
confidence: 99%